The output of the fifty years' scientific activity of Prof. Dr. Jerzy Ranachowski - I. MALECKI (Archives of Acoustics)
Professor Jerzy Ranachowski began his research as an assistant at the Electrical Faculty of the Technical University in Wrocław under the guidance of Professor J. Skowroński.